2011
DOI: 10.1074/jbc.m110.210443
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cθ Is a Specific Target for Inhibition of the HIV Type 1 Replication in CD4+ T Lymphocytes

Abstract: The novel protein serine/threonine kinase C (PKC) isoform is selectively expressed in T lymphocytes but not B lymphocytes, erythrocytes, polymorphonuclear neutrophils, monocytes, or macrophages (1). Other PKC isotypes (␣, ␤, ␦, ⑀, , and ) are also expressed in T cells, but PKC is essential for T cell receptor/CD3-mediated activation events (2, 3). Among novel PKCs, PKC displays the highest amino acid similarity with PKC␦, not only in the catalytic or kinase core and the diacylglycerol binding regulatory domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…Moreover, the results obtained with rottlerin were compatible with those obtained utilizing more selective approaches to inhibit PKCδ in a previous report (17). It was recently reported rottlerin also inhibited PKCθ (23). However, our data indicates that PKCθ is not involved PMA-induced glucagon secretion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the results obtained with rottlerin were compatible with those obtained utilizing more selective approaches to inhibit PKCδ in a previous report (17). It was recently reported rottlerin also inhibited PKCθ (23). However, our data indicates that PKCθ is not involved PMA-induced glucagon secretion.…”
Section: Discussionsupporting
confidence: 79%
“…2). It was recently reported that rottlerin also inhibited PKCθ another nPKC isoform, with IC50 of 1.6 μM and less than 3 μM of rottlerin selectively inhibited PKCθ (23). PMA-induced glucagon secretion was not suppressed by less than 2.5 μM of rottlerin, suggesting that PKCθ was not involved in PMA-induced glucagon secretion (Fig.…”
Section: Effect Of Quercetin On Glucagon Secretion From Isolated Isletsmentioning
confidence: 94%
“…In contrast, the PKC u inhibitor Rottlerin did not inhibit wild-type CD4/WC1 endocytosis, even at the high dose of 10 mM, which inhibits PKC u, d, and z (Fig. 4A) (36). These results suggest that phosphorylation by PKC a or b, but not by PKC u, d, or z, is necessary for optimal WC1 endocytosis in Jurkat T cells; additionally, although phosphorylation of S13 or S14 is not required for PMA-induced endocytosis in Jurkat T cells (Fig.…”
Section: Pkc Inhibitor Reduces Endocytosis Of Cd4/wc1mentioning
confidence: 95%
“…Because the serine mutant CD4/WC1S13A/S14A reduced PMAinduced endocytosis when it was expressed in 293T cells but not in Jurkat T cells, we investigated whether WC1 endocytosis in Jurkat T cells was independent of serine/threonine phosphorylation by PKC using the inhibitors Gö6983 and Rottlerin (36). The PKC a, b, d, or z inhibitor Gö6983 significantly reduced the PMAinduced endocytosis of wild-type CD4/WC1 (Fig.…”
Section: Pkc Inhibitor Reduces Endocytosis Of Cd4/wc1mentioning
confidence: 99%
“…Strikingly, inhibition of PKCh through the use of rottlerin prevented PKCh translocation to lipid rafts, repressed NF-kB, and reduced HIV-1 replication more than 20-fold in MT-2 and Jurkat cells and more than 4-fold in peripheral blood lymphocytes [131]. Interestingly, PKCh has recently been shown to mediate T cell gene expression (i.e.…”
Section: Ampk Activation and Mitochondrial Atp Production Is Essentiamentioning
confidence: 96%